(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article talks about the science of education taught as a textbook to primary school students and its importance, teaching methods and relevance of the science. It was mentioned about the order and teaching methodology of the lessons conducted by the teachers, the scope and consistency of the practical exercises.